2016
DOI: 10.12809/hkmj144390
|View full text |Cite
|
Sign up to set email alerts
|

Babesiosis acquired from a pet dog: a second reported case in Hong Kong

Abstract: A 61-year-old Chinese man was admitted to our hospital in June 2012 with a 2-week history of fever and chills. After admission, he developed hypotension and respiratory distress and was transferred to the intensive care unit (ICU) for further management.He frequently commuted between New York, Hong Kong, and Shanghai for business. He lived in his own house in New York and had a dog. Three weeks before onset of his symptoms, he swept his basement where his dog spent most of its time. He was not aware of any tic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Despite the wide distribution of this “old” infection and the fact that the virus can be present for about one week in the blood of infected patients, the risk of dengue fever as a transfusion- or graft-transmitted disease emerged only recently [ 35 ]. The first documented case of post-transfusion dengue was observed in Hong Kong in 2002, but was only published in 2008 [ 36 ]. Between 2002 and 2019, a total of seven papers reported on 15 cases of the possible transmission of DENV to 15 recipients, with different levels of accountability [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Dengue Virusmentioning
confidence: 99%
“…Despite the wide distribution of this “old” infection and the fact that the virus can be present for about one week in the blood of infected patients, the risk of dengue fever as a transfusion- or graft-transmitted disease emerged only recently [ 35 ]. The first documented case of post-transfusion dengue was observed in Hong Kong in 2002, but was only published in 2008 [ 36 ]. Between 2002 and 2019, a total of seven papers reported on 15 cases of the possible transmission of DENV to 15 recipients, with different levels of accountability [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Dengue Virusmentioning
confidence: 99%
“…transmission to humans a much higher possibility. Lastly, pet dogs living within the same household were incriminated for at least two cases of human babesiosis in the literature [80,81]. One needs to be cautious in interpreting this finding as no evidence presented linked those dogs directly to human infections.…”
Section: Possible Roles Of the Domestic Dog In Human Babesiosismentioning
confidence: 99%
“…Certainly, this would not help the government to deliver effective governance. As Chan (2013) observes, organic bonding between leadership of the executive and political parties from the legislature is a much-needed condition for effective governance (p. 86). Second, as the LegCo is returned by both direct and indirect elections, it commands a higher degree of popular mandate than the executive.…”
Section: Changes To Institutional Designs and Rules That Govern The Formation And Operation Of The Legco And Their Impacts On Its Performmentioning
confidence: 99%
“…A plausible answer to this question lies in the institutional design that the Basic Law has provided for the HKSAR. Well-documented studies have demonstrated that the performance of political institutions and their relations will inevitably be affected by changes to institutional designs and rules that govern them (Weaver and Rockman, 1993; Chan, 2013; Cheung, 2002, 2004, 2007; Lam, 2013; Lui, 2012). This is also the case in the HKSAR.…”
Section: Introductionmentioning
confidence: 99%